Analisis Kesesuain Penerapan Model Promblem Based Learning dengan Sintaks Pembelajaran di Kelas VI Sekolah Dasar - Septri Larissa; Syakhilla Pratiwi; Felia Hafifah; Ibisanti Fatikasari; Hasanah; Reinita (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to analyze the conformity between the implementation of the Problem-Based Learning (PBL) model and its instructional syntax in a sixth-grade classroom at SD Negeri 02 Cupak Tangah, Padang City. A descriptive qualitative approach was employed, with data collected through interviews and documentation. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that PBL promoted student-centered learning through discussion, inquiry, and presentation activities. Four stages of the PBL syntax were implemented effectively, while the analysis and evaluation stage was not optimally conducted. The overall implementation level reached approximately 75%. The main challenges included limited instructional time, inadequate learning facilities, and varying levels of student participation. Nevertheless, PBL positively contributed to students’ engagement, collaboration skills, presentation abilities, and learning motivation. The limitation of this study lies in its focus on a single school and the use of interview and documentation data only. Future studies are recommended to involve a wider range of schools and incorporate direct classroom observations to provide a more comprehensive understanding of PBL implementation.